Analisa Sistem Kepegawaian di PT. Primo St Moritz dengan Metode Waterfall - Saputra, Herdiansyah; Saputra, Ade Sony; Judin, Sirat; Husaini, Vandy Sadam; Saifudin, Aries; Desyani, Teti (Jurnal Informatika Universitas Pamulang, 2021)
Primo Supermarket St Moritz is a retail company that runs its business in the field of selling basic necessities, where the staffing system is still not integrated, such as an attendance system that uses fingerprints as identification or a finger print machine that is not connected to other systems so that the attendance input process is still done repeatedly, which results in errors in payroll calculations because the salary data has not been connected to the attendance system so that the salary calculation is not precise and inaccurate, then there is also a leave application that is still manual, which fills out the leave form in writing and is only stored in a folder so that leave forms can be scattered and unsafe, as well as difficulties in preparing attendance data reports, salary data reports, and leave data reports which take quite a long time because the system has not been connected automatically. In this study, we will design a web-based academic information system using Codeigniter, using the waterfall method with PHP and MySQL programming languages for the database, with the aim of creating an attendance system that is connected to the salary system, simplifying the calculation of employee salaries, so that the calculation process becomes more efficient. fast, precise, and accurate, create an online leave application system that makes it easier to make attendance data reports, salary data reports, and leave data reports.